Report of two novel mutations in PTHLH associated with brachydactyly type E and literature review. Issue 3 (6th December 2015) - Thomas‐Teinturier, Cecile; Pereda, Arrate; Garin, Intza; Diez‐Lopez, Ignacio; Linglart, Agnès; Silve, Caroline; de Nanclares, Guiomar Pérez
Abstract : Autosomal‐dominant brachydactyly type E is a congenital limb malformation characterized by small hands and feet as a result of shortened metacarpals and metatarsals. Alterations that predict haploinsufficiency of PTHLH, the gene coding for parathyroid hormone related protein (PTHrP), have been identified as a cause of this disorder in seven families. Here, we report three patients affected with brachydactyly type E, caused by PTHLH mutations expected to result in haploinsufficiency, and discuss our data compared to published reports. © 2015 Wiley Periodicals, Inc.